Evaluating Prospective Homestay Families in the U.S. and New Approaches to Further Enrich the Exchange Student’s Opinion of America (Global Journal of Human-Social Science, 2021)
Determining the level of effectiveness in exchange programs has become increasingly more important to evaluators Likewise bilateral connectivity between the host country s people institutions and the exchange student have benefitted from recent recommendations of comprehensive evaluations However the homestay family factor of the exchange experience lags in this area In that regard exchange programs could improve significantly from a broader and deeper understanding of the homestay experience as seen from the host s perspective In fact citizen diplomacy is alive and active in the host s homes People to people contact in these intimate settings can form attitudes sentiments and emotional attachments that should be measured as a mode to improve citizen diplomacy practices From the aptitude of the host family to their level of community engagement several elements are key to an ambiance where the exchange student can better adapt learn interact feel think express ideas learn about customs and community familiarize with the language and overall enhance their experience hence their opinion about their host country